Climate change adaptation: tips for effective information sharing and networking - Global Adaptation Network (2015)
Climate change adaptation is a multidisciplinary undertaking, requiring collaboration from diverse actors who operate in different sectors. This makes it critical to share information and share it well. Informed by a forum organized by the Global Adaptation Network (GAN) that was attended by nearly one hundred participants, this brief looks at tools, activities, and techniques for effective knowledge sharing through adaptation networks.